WEB-BASED SALES INFORMATION SYSTEM AT TOKO MANDIRI ELECTRONIC USING SOFTWARE DEVELOPMENT LIFE CYCLE (SDLC) METHOD - Andreas Tarigan (Bahasa Indonesia, 2022)
Toko Mandiri Elektronik is an electronics store in binjai that sells various types of electronics. Stores still use conventional methods (brochures, mouth to mouth). if there are additional items, the store must also manually change the item catalog to the store catalog. this research provides a solution for designing a website-based system that makes it easier for Toko Mandiri Elektronik in the product marketing process that can increase sales of electronic products at Toko Mandiri Elektronik. System development used by the author in analyzing the system using the SDLC method. The system generates a sales report in the form of a table which is useful for stores in searching data. The store catalog system is already in the form of a database, so the search process for product data will be faster and clearer.